Groundwater Quality on the Adriatic Karst Island of Mljet (Croatia) and Its Implications on Water Supply - Staša Borović; Josip Terzić; Marco Pola (Geofluids)
Water supply of the islands is a global challenge, especially in the countries which have highly indented coastlines with numerous islands. The island of Mljet in Croatia was investigated due to its unique source of water supply: desalination of water from brackish lakes—blatinas—fed by groundwater and connected to the sea by karst conduits. Water sampling and chemical analyses were performed during hydrological minimum and maximum with regard to groundwater levels in 2005/2006 and minimum in 2016. A total of 13 samples were analysed within the study: 10 samples were taken from blatinas, 1 from pit well, and 2 from borehole wells. All waters sampled from the lakes are of Na-Cl type. The seawater percentage in the lakes used to extract feed water for desalination plants, calculated by conservative mixing approach, is relatively low (0.7-9.8%) and varies in correlation with hydrological seasons. Low proportion of seawater is an essential factor of cost minimisation in desalination by the installed reverse osmosis (RO) plants. Daily monitoring of total dissolved solids in the feed water was introduced in May 2016, and its results were analysed in the context of precipitation—a sole source of island aquifer recharge. Maximum concentrations were observed during September and interpreted to be caused by a combination of natural and anthropogenic pressure during the summer tourist season. Minimum concentrations were expected after the rainy season in the cold part of the year but were observed in June instead. Due to a short observation period and untypical distribution of precipitation in the same time interval, the data can only be considered indicative. An unusual pattern of sulphate anion concentrations, which cannot be attributed solely to fresh- and seawater mixing, was observed in one of the blatinas, but its origin could not be determined based on available data. Taking into account all the presented data on groundwater quality, climate change predictions, the connection of water supply system to the mainland and problems with the effluent treatment, it is clear that the main future challenge will be the creation of an island-wide sustainable water management plan followed by continuous monitoring and research.